Point prevalence of incontinence-associated dermatitis and associated factors in critical patients (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To identify the prevalence of incontinence-associated dermatitis (IAD) and its associated factors in critically ill patients. Method: A cross-sectional, quantitative study conducted in the Intensive Care Unit of a private hospital in São Paulo, involving 93 patients who met the eligibility criteria. Data collection took place on a single day in December 2016, with a thorough review of medical records and assessments of hospitalized patients. A three-part instrument was used: 1) sociodemographic data, 2) urinary and fecal elimination, and 3) characterization of IAD. The analysis was performed using descriptive and inferential statistics. Results: Of the 93 patients, 50.5% were women, aged 19 to 104 years. IAD was identified in 40.9% of patients, with a higher prevalence in the intensive care unit (66.7%). Erythema was the most common manifestation (89.4%), and the perianal region was the most affected area (76.3%). The use of antibiotics (p=0.004), corticosteroids (p=0.001), mechanical restraint (p=0.006), fecal incontinence (p